Russell, Hugo & Ayliffe's principles and practice of disinfection, preservation and sterilization - Fraise, Adam P.; Maillard, J.-Y.; Sattar, Syed. (Chichester : Wiley-Blackwell, 2013)
The new edition of this established and highly respected text is THE definitive reference in its field. It details methods for the elimination or prevention/control of microbial growth, and features: New chapters on bioterrorism and community healthcareNew chapters on microbicide regulations in the EU, USA and CanadaLatest material on microbial resistance to microbicidesUpdated material on new and emerging technologies, focusing on special problems in hospitals, dentistry and pharmaceutical practicePractical advice on problems of disinfection and antisepti.
Section 1. Principles. Historical Introduction / Adam P. Fraise -- Types of Microbicidal and Microbistatic Agents / Ibrahim Al-Adham, Randa Haddadin, Phillip Collier -- Factors Affecting the Activities of Microbicides / Jean-Yves Maillard -- Biofilm Recalcitrance : Theories and Mechanisms / Andrew J. McBain, Najib Sufya, Alexander H. Rickard -- Mechanisms of Action of Microbicides / Peter A. Lambert -- Mechanisms of Bacterial Resistance to Microbicides / Jean-Yves Maillard -- Resistance of Bacterial Spores to Chemical Agents / Peter Setlow -- Testing of Chemicals as Mycobactericidal Agents / Syed A. Sattar -- Fungicidal Activity of Microbicides / Sara Fernandes, Marta Simoes, Nicolina Dias, Cledir Santos, Nelson Lima -- Sensitivity and Resistance of Protozoa to Microbicides / Vincent Thomas -- Virucidal Activity of Microbicides / Jean-Yves Maillard, Syed A. Sattar, Federica Pinto -- Transmissible Spongiform Encephalopathies and Decontamination / Gerald McDonnell -- Microbicides : The Double-Edged Sword : Environmental Toxicity and Emerging Resistance / Jean-Marie Pages, Jean-Yves Maillard, Anne Davin-Regli, Susan Springthorpe -- Section 2. Practice. Evaluation of Antimicrobial Efficacy / Lawrence Staniforth -- Assessing the Efficacy of Professional Healthcare Antiseptics : A Regulatory Perspective / Albert T. Sheldon -- Legislation Affecting Disinfectant Products in Europe : The Biocidal Products Directive and the Registration, Evaluation and Authorization of Chemicals Regulations / Jennifer A. Hopkins -- Regulatory Authorization of Hard Surface Disinfectants in Canada / Andre G. Craan, Ian A. Chisholm, Shannon C. Wright -- United States Regulation of Antimicrobial Pesticides / Sally Hayes -- Heat Sterilization / Charles O. Hancock -- Radiation Sterilization / Peter A. Lambert -- Gaseous Sterilization / Jean-Yves Dusseau, Patrick Duroselle, Jean Freney -- Gas Plasma Sterilization / Gerald McDonnell -- Filtration Sterilization / Susannah E. Walsh, Stephen P. Denyer -- New and Emerging Technologies / Peter A. Burke, Gerald McDonnell -- Preservation of Medicines and Cosmetics / Sarah J. Hiom -- Sterility Assurance : Concepts, Methods and Problems / Richard Bancroft -- Hand Hygiene / Benedetta Allegranzi, Didier Pittet -- Decontamination of the Environment and Medical Equipment in Hospitals / Adam P. Fraise -- Decontamination of Endoscopes / Michelle J. Alfa, Christina Bradley -- Issues Associated with the Decontamination of Laundry and Clinical Waste / Peter Hoffman -- Treated Recreational Water Venues / Darla M. Goeres, Philippe Hartemann, John V. Dadswell -- Antimicrobial Surfaces / Gareth J. Williams -- Antimicrobial Devices / Brendan F. Gilmore, Sean P. Gorman -- Antimicrobial Dressings / Valerie Edwards-Jones -- Antimicrobial Textiles and Testing Techniques / Robert A. Monticello, Peter D. Askew -- Use of Microbicides in Disinfection of Contact Lenses / Patrick J. McCormick, Susan E. Norton, James J. Kaiser -- Special Issues in Dentistry / Jonathan L.S. Caplin -- Natural Products / Rose Cooper -- Applications of Bacteriophage Technology / Geoffrey W. Hanlon -- Control of Infectious Bioagents / Les Baillie, Steven Theriault.
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Disinfection and disinfectants; Sterilization; Preservation of materials; Disinfection -- methods; Sterilization -- methods; Anti-Infective Agents; Preservatives, Pharmaceutical; Drug Resistance, Microbial; Decontamination; Anti-Infective Agents; Decontamination; Disinfection -- methods; Drug Resistance, Microbial; Preservatives, Pharmaceutical; Sterilization -- methods; MEDICAL -- Epidemiology; MEDICAL -- Health Risk Assessment; Disinfection and disinfectants; Preservation of materials; Sterilization; Electronic books